Activation of REG family proteins in colitis - Granlund, Atle Vand Beelen (Informa Healthcare, 2011)
AIMS: To do a genome-wide gene expression study of active and inactive ulcerative colitis and Crohn's disease (inflammatory bowel disease – IBD) and examine the most differentially expressed genes. As the study showed an extreme upregulation of all regenerating islet-derived genes (REG proteins) in active IBD, we further studied the expression of REGs on protein level in active and inactive IBD, as well as in non-IBD (pseudomembranous) colitis. METHODS: Microarray analysis was done on a total of 100 pinch biopsy samples from healthy controls and patients with Crohn's disease or ulcerative colitis. Tissue samples from IBD and pseudomembranous colitis were examined with routine histology and immunohistochemical analysis for REGIα, REGIV, DEFA6, and serotonin. RESULTS: REG mRNAs were up to 83 times overexpressed in diseased mucosa compared with mucosa from healthy individuals. REGIα and REGIV were overexpressed at immunohistochemistry and located to different mucosal cell types. REGIα was expressed in basal half of crypts, REGIV in mid and outer parts of crypts and in surface epithelium and seems to be stored in, and secreted from, goblets. Pseudomembranous colitis samples showed similar staining patterns, and some IBD samples stained REG positive without inflammation on routine histology. CONCLUSIONS: All REG family mRNAs are upregulated in IBD. REGIα and REGIV have different cellular localization, possibly reflecting different biological functions. REG protein expression also in pseudomembranous colitis shows that REG family proteins are regulated in inflammatory injury and repair, not specifically for IBD as previously thought.